Outcome of Vertical Skeletal Pattern in the Buccal Corridor Area Show during Posed Smile - Fasila Rashid, Amna Bilal, Namrah Bashir, Rashid Hassan (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine link between a patient’s buccal relationship and vertical skeletal corridor region display during a posed grin. Study design: Descriptive study. Place and duration of study: Department of Orthodontic, Ayub Dental College from 1st July 2022 to 31st December 2022. Methodology: One hundred and seventy patients with normal, additional and insignificant buccal corridors were enrolled. The patient’s Frankfort Horizontal plane parallel to the floor, their lips relaxed, and their teeth in centric occlusion, lateral cephalograms were obtained. Results: The measurement of the buccal corridor area visible during a frontal grin varies from 0 mm to 4.50mm. The average size of the buccal corridor was 1.799±0.9904 mm. The ratio of lower anterior facial height towards total anterior facial height ranged from 48° to 67° with mean anterior facial height was 45.246±2.48. Conclusion: Lower anterior facial height has a substantial impact on how much of the buccal corridor region shows during posed smiles, and a rise in ratio causes less buccal corridor area to display. Keywords: Inter-commissure width, Inter-pre-molar width, Inter-pupillary distance